Global prevalence of non-perennial rivers and streams - Messager, Mathis Loïc; Lehner, Bernhard; Cockburn, Charlotte; Lamouroux, Nicolas; Pella, Hervé; Snelder, Ton; Tockner, Klement; Trautmann, Tim; Watt, Caitlin; Datry, Thibault (Nature (London), 2021)
Flowing waters have a unique role in supporting global biodiversity, biogeochemical cycles and human societies 1 – 5 . Although the importance of permanent watercourses is well recognized, the prevalence, value and fate of non-perennial rivers and streams that periodically cease to flow tend to be overlooked, if not ignored 6 – 8 . This oversight contributes to the degradation of the main source of water and livelihood for millions of people 5 . Here we predict that water ceases to flow for at least one day per year along 51–60 per cent of the world’s rivers by length, demonstrating that non-perennial rivers and streams are the rule rather than the exception on Earth. Leveraging global information on the hydrology, climate, geology and surrounding land cover of the Earth’s river network, we show that non-perennial rivers occur within all climates and biomes, and on every continent. Our findings challenge the assumptions underpinning foundational river concepts across scientific disciplines 9 . To understand and adequately manage the world’s flowing waters, their biodiversity and functional integrity, a paradigm shift is needed towards a new conceptual model of rivers that includes flow intermittence. By mapping the distribution of non-perennial rivers and streams, we provide a stepping-stone towards addressing this grand challenge in freshwater science. Non-perennial rivers and streams are mapped globally, showing that more than half of rivers worldwide experience no flow for at least one day per year.